Measures aimed at countering corruption offenses offi cers (Journal of actual problems of jurisprudence, 2019)
On scientific work, that was named, to perfect questions of anticipating voracity and her a right protects efficiencyapplication in experience office workers of organs examined theoretical approach lines increase. And also fight andmeasures of anticipating to renew voracity, according to conclusions in character of suggestion, examined questionsintroduction dowry and in laws.Key words: Corruption, corruption crimes, post crimes, counteractions of corruption, fi ght against a corruption.